2017
DOI: 10.17796/1053-4628-41.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals in Biostatistics for Research in Pediatric Dentistry: Part I – Basic Concepts

Abstract: The purpose of this report was to provide the reader with some basic concepts in order to better understand the significance and reliability of the results of any article on Pediatric Dentistry. Currently, Pediatric Dentists need the best evidence available in the literature on which to base their diagnoses and treatment decisions for the children's oral care. Basic understanding of Biostatistics plays an important role during the entire Evidence-Based Dentistry (EBD) process. This report describes Biostatisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Data was explored for normality using Kolmogorov-Smirnov test of normality. The results of Kolmogorov-Smirnov test indicated that most of the data was normally distributed (parametric data), therefore independent t test was used for intergroup comparison, while intragroup comparison (before, after and within the same group) was performed using paired t-test (10,11) . The significance level was set at p≤0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was explored for normality using Kolmogorov-Smirnov test of normality. The results of Kolmogorov-Smirnov test indicated that most of the data was normally distributed (parametric data), therefore independent t test was used for intergroup comparison, while intragroup comparison (before, after and within the same group) was performed using paired t-test (10,11) . The significance level was set at p≤0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The significance level was set at p≤0.05. Statistical analysis was performed with SPSS 19.0 (Statistical Package for Scientific Studies, SPSS, Inc., Chicago, IL, USA) for Windows (10,11) .…”
Section: Discussionmentioning
confidence: 99%